Propagação e conservação in vitro de bromélias do gênero Aechmea de valor ornamental - Rosa, Sandra Santa (2010)
The increasing use of bromeliads as ornamental plants and the growing interest in gardening with native species have favored the illegal extraction of species in this family. Aechmea blanchetiana (Baker) L. B. Smith, Aechmea distinchanth Lemaire and Aechmea leptantha (Harms) Leme & JA Siqueira are native bromeliads with ornamental potential. Without a crop production system the predatory extraction have been growing in the last years and has leading this species to threatened conditions. The aim of this study was to develop na efficient system to plant production using micropropagation techniques to A. blanchetiana and A. distichantha and an in vitro conservation system of these species and A. leptantha. In vitro germination was performed and evaluated under presence or absence of light. On the multiplication phase the effect of different plant growth regulators were evaluated. Plants were cultivated on MS medium supplemented with 0.05 and 0.5 μM NAA in combination with 2.2 and 4.4 μM of BAP or KIN. To establish the in vitro conservation protocol three concentrations of MS salts were tested (MS, 1/2 MS and 1/3 MS) and two incubation condition were evaluated: the growth chamber and the conservation chamber with different temperatures, light intensity and photoperiod for 3 species of Aechmea (A. leptantha, A. and A. blanchetiana distichantha). Seeds of A. blanchetiana and A. distichantha presented photoblastic behavior with 98.85% and 62.09% of germination respectively under light condition. All treatments formed adventitious buds, and the MS medium supplemented with 0.5 μM NAA + 2.2 μM BAP promoted the best multiplication rates in both species. The BAP promoted the formation of shoots without roots, while KIN favored higher rooting at the expense of the shoot number. The results showed that it is possible to keep under slow growth for twelve months, plants of A. leptantha, A. blanchetiana and A. distichantha in media culture with 1/3 MS in conservation chamber (temperature of 22 } 2°C, 22 μmol m-2 s-1 of photon flux density and 12h photoperiod).